(untitled) (Bangladesh Veterinarian, 2015)
Studies on skin closure techniques are scarce in veterinary practice. The aesthetic result of a skin suture is hardly considered in ruminants. This study was designed to compare the morphological characteristics and outcome of incised skin wounds closed with three suture patterns using two suture materials. Simple interrupted (SI), cross mattress (CM) and horizontal mattress (HM) suture patterns were used with nylon and silk to close incised skin wounds. A total of 54 surgical wounds were made in nine cattle. Follow-up information was obtained up to day 30 postoperatively. Area of wound, elevation of suture line from the skin surface, width of suture area and contraction length per week was recorded. Silk caused more tissue reaction and suture marks than nylon. Simple interrupted suture produced good apposition but showed suture marks. Horizontal mattress caused marked tissue swelling, inflammation, sloughing of cutting edges due to prominent eversion and strangulation of cutting edges and produced prominent scar. Cross mattress produced good apposition with sufficient eversion of cutting edges and good cosmetic appearance with fewer suture marks. It is suggested that cross mattress pattern with nylon could be a better choice for closing skin wounds in ruminants. This study could help veterinary surgeons to consider appropriate suture technique and materials for skin closure. DOI: http://dx.doi.org/10.3329/bvet.v31i1.22840 Bangl. vet. 2014. Vol. 31, No. 1, 27-37